Social Development of Underprivileged Sections of the Society and Management of the Government - Fulmali, Kanchan S. (SFIMAR Research Review, 2016)
In India, the backward classes' movement has passed through various stages and each stage is characterized by different aims and objectives. During the medieval period i.e. before the advent of the British regime, the caste system was so rigid that mobility within it was very difficult. Shudras are the deprived people who did not acquire education in those days. They were lagging behind in education so they did not get proper jobs, resulting in loss of their income. Now they are far behind the others. It is necessary to educate them and bring them up. Today, in India, literacy rate is lower amongst the SC which is 54.69% and amongst ST which is 47.10% compared to General Literacy rate which is 64.84%. There are several reasons like parents' disliking education because they are illiterate, casual approach towards education and mainly poor financial position. It increases their dropout rate and their enrolment in higher education is reducing. So the Management of the Government of financial aid is a must for the proper justification. The Economic Survey 2009-10 released by the Finance Minister on the 25/2/2010 in the parliament, points out that the implementation of the schemes for the SC/ST have not met the targets. Out of total annual expenditure Rs. 10,20,838 Cr for the financial year 2009-10, the Union of India spent 13.36% in Social Service Sector in both the Plan and non-plan budgets. That means Management of the Government is lacking somewhere. The paper is focused on how the educationally deprived people should rise above their poverty and untouchability. Education is one of the areas that is help for social reforms and the development of these people. But for the education Management of the Government through the announcement of the policies for financial aids is required. It shows educational opportunities and challenges for this class and proves that education is helping to bring social reforms and their development.